A culture of silence: a study of a social emotional learning (SEL) intervention for teenages affected by domestic violence. - SWEETMAN, NORAH JOAN (Trinity College Dublin. School of Education. Discipline of Education, 2019)
This study explores the effects of domestic violence on teenagers’ social emotional development. The young peoples’ perspective on their experience, and how it affected them, is explored by means of an active social emotional learning (SEL) programme. The complexity of the collection of prevalence figures and the public reluctance to discuss domestic violence, create an intense culture of silence for victims. This extends from intrafamily to professional and supportive relationships and those they meet with in society. The initial research inquired into community awareness levels around domestic violence and existing supports for teenage victims. This resulted in the development of ‘up2talk’; a ten week programme of social emotional learning (SEL). This was hosted in a family services centre and aimed to enhance the five teenage participants’ communication and assertiveness skills to process and express their experience. The focus of the study was on voice and choice for the teenagers at every stage of the programme and follow up interviews. was related to the research highlighting the uniquely individual experience of domestic violence for each family. This approach was based on theories of social constructivism. The group sharing and support offered during the group ‘up2talk’, concerning domestic violence experiences, was from a SEL perspective, not that of a therapeutic intervention. The participants used the third person: ‘a young person might feel’ or representations of emotion through art and drama. This maintained emotional safety and ensured that the process was participant led. The findings showed a deeply embedded level of silence. Their awareness of changes in their communication suggested that young people are more capable of deciding on appropriate supports and levels of engagement than is commonly accepted. The high levels of self-blame expressed by these capable young people, achieving well in school and leisure activities, highlighted the fragility of apparent resilience. A key finding was the need to enable the voice of young people affected by violence. The ‘plan, do and review’ method used in ‘up2talk’ could research effective implementation of the Social Personal Health Education (SPHE) programme in schools, and also reach young victims impacted by self-blame. The study identified the central role silence had in denying them voice. Suggestions for established modules and organisations to involve young people directly in the enacting of a platform for their voice and needs are outlined. Direct involvement in the design of materials and outreach programmes concerning key issues around domestic violence, including addiction and mental health, have been regularly requested by students reviewing SPHE. The value of this direct participation and feedback was evident in the process and impact of this programme ‘up2talk’.
APPROVED
Keywords: trauma informed workshops; adolescent trauma; intergenerational effects of domestic violence; social skills in recovery for teenagers